2010
DOI: 10.5194/acp-10-6711-2010
|View full text |Cite
|
Sign up to set email alerts
|

Estimating the maritime component of aerosol optical depth and its dependency on surface wind speed using satellite data

Abstract: Abstract. Six years (2003Six years ( -2008 of satellite measurements of aerosol parameters from the Moderate Resolution Imaging Spectroradiometer (MODIS) and surface wind speeds from Quick Scatterometer (QuikSCAT), the Advanced Microwave Scanning Radiometer (AMSR-E), and the Special Sensor Microwave Imager (SSM/I), are used to provide a comprehensive perspective on the link between surface wind speed and marine aerosol optical depth over tropical and subtropical oceanic regions. A systematic comparison between… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
49
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(54 citation statements)
references
References 44 publications
5
49
0
Order By: Relevance
“… Lehahn et al [2010] reported that, on average, the threshold value of surface wind speed for triggering emission of maritime aerosols is 4.1 ± 0.1 m/s. When wind speed exceeds the threshold value, the coarse‐mode marine aerosols' optical depth is linearly correlated to the surface wind speed, with a consistent slope of 0.009 ± 0.002 m/s [ Lehahn et al , 2010]. Thus, knowledge of wind speed and direction assists in estimating the average background wind‐induced marine aerosol loading in the lower part of SA.…”
Section: Resultsmentioning
confidence: 99%
“… Lehahn et al [2010] reported that, on average, the threshold value of surface wind speed for triggering emission of maritime aerosols is 4.1 ± 0.1 m/s. When wind speed exceeds the threshold value, the coarse‐mode marine aerosols' optical depth is linearly correlated to the surface wind speed, with a consistent slope of 0.009 ± 0.002 m/s [ Lehahn et al , 2010]. Thus, knowledge of wind speed and direction assists in estimating the average background wind‐induced marine aerosol loading in the lower part of SA.…”
Section: Resultsmentioning
confidence: 99%
“…Stronger correlations have been observed using the wind speed averaged over some time before the aerosol measurements were made (‘wind speed history’), rather than instantaneous wind speed, as wind changes on timescales shorter than aerosol lifetimes. The strongest correlations are typically found with wind speed averaged for 12–24 hours prior to the AOD measurement [ Gathman , 1983; Hoppel et al , 1990; Smirnov et al , 2003b; Lehahn et al , 2010]. Some of these analyses bin data by wind speed, and then fit binned averages; this binning will naturally lead to stronger correlations than fits using all data points, as the variability is somewhat averaged‐out, so this should be borne in mind when examining regression statistics from different studies.…”
Section: Relationship With Meteorological Parametersmentioning
confidence: 99%
“…Some studies suggest a linear relationship [32][33][34][35], while others a power-law relationship [14,36,37] or an exponential relationship [38]. The discrepancy between different relationships is probably attributed to different instrumentations, platforms, locations and periods used in the investigations.…”
Section: Introductionmentioning
confidence: 99%